Public Health Evaluation of COVID-19 Vaccine Acceptability and Health Behaviors in South Africa: Past, Current, and Future Implications (2020–2022) - Handan Wand; Jayajothi Moodley; Tarylee Reddy; Sarita Naidoo (Advances in Public Health)
South Africa is facing a high burden of COVID-19 pandemic with low-vaccine coverage in the African Region. We aimed to investigate the temporal changes and impacts in health behaviors on vaccine acceptability in pre-, during-, and post-vaccine roll-out periods. In this cross-sectional study, we used the combined data from the nationally conducted “COVID-19 Vaccine Surveys (CVACS)” (May 2020–February/March 2022). Semiparametric regression models were used to capture the nonlinear association between the vaccine acceptability and health behaviors. Our study provided compelling evidence for a substantial decline in COVID-19 vaccine trust which shifted from 62%–70% to 26%–42% overtime. Participants younger than 40 years of age were less likely to receive the vaccine before it became available. However, this association changed in the postvaccine period with significant uptake in vaccine acceptance in younger groups. South Africans who identified themselves as black were more likely to intend to receive (aORs ranged: 1.93−3.60) and to trust the vaccine’s safety and efficacy (aORs ranged:1.79−1.23) in all time periods. “Mask wearing” and “frequent hand washing” were the most commonly reported behaviors. Given the lower rates of vaccine acceptability and a reduction in preventative health behaviors, monitoring the spread of infections is crucial and may have significant clinical and epidemiological implications.